Concept of sensory garden in the revitalization project of a housing estate in Krasnystaw - Dudkiewicz, Margot; Krupiński, Patryk; Czapla, Sylwia; Moryc, Cyprian (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
Sensory gardens are places designed to stimulate the senses. Most often they are designed near hospitals and schools, where due to availability of the garden, people suffering from sensory processing disorders (autism, dementia, depression) can enjoy new experiences in a safe and comfortable environment. The purpose of the study was to show the possibility of introducing a sensory garden also to the housing estate. The city of Krasnystaw is located 50 km south of Lublin. By carrying out an inventory of existing vegetation and study work, project guidelines were developed. One of the social aspects of the work was to create a garden, that is to integrate the residents. The plant material was selected having in mind senses specification, including hearing, smell and sight. Architectural elements (lighting, benches, gazebo) that were missing so far have been designed, using mainly natural materials – stone and wood. The project selected decorative species of trees and shrubs in terms of colors and forms of leaves, flowers, fruits and an interesting conformation.